High temperature effect on the mechanical behavior of steel fiber reinforced self-compacting concrete containing ground pumice powder - Karatas, Mehmet; Dener, Murat; Benli, Ahmet; Mohabbi, Mehrzad (Ernst & Sohn, 2019)
This study reports the results of high temperature effects on the properties of steel fiber reinforced self-compacting concrete (SFRSCC) fabricated by replacing cement with ground pumice powder (GPP) as mineral additive at different substitution rates. The mixtures had the same amounts of steel fiber and the binding material with constant water to binder (w/b) ratio of 0.37. In this context, five SFRSCC series were prepared by replacing Portland cement (PC) with 5, 10, 15, and 20% of GPP including the control mix. Sixty cube samples with a dimension of 150 x 150 x 150 mm were fabricated and exposed to curing aged 3, 7, 28, and 90 days to conduct compressive strength tests and a total of 100 x 100 x 350 mm 18 beam samples cured at 28 days were fabricated to perform the flexural strength tests. Durability tests were performed on the 18 cube samples of 100 x 100 x 100 mm subjected to water curing at 28 days. In addition, the relation between the compressive strength and Ultrasonic Pulse Velocity (UPV) of SFRSCC samples was compared aged 1, 3, 14, and 28 days. Samples of SFRSCC were subjected to the temperatures of 200, 400, 600, and 800 degrees C after being cured at 28 days then cooled to room temperature before conducting tests. The results revealed that the compressive strength of all SFRSCC mixes enhanced at 200 degrees C by 5.34 and 3.55% for control and GPP10 mixes respectively. The strength loss of mixes incorporating GPP is about 60% at 800 degrees C.
Keywords: compressive strength; elevated temperature; ground pumice powder; steel fiber reinforced self-compacting concrete; UPV